FAKTOR-FAKTOR UNDERPRICING INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Kartika, Gusti Ayu Sri; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Underpricing is phenomena in huge a part of stock price IPO in Indonesia Stock Exchange (IDX).  Underpricing avoid by companies because doesn’t earn maximum fund, in the other hand investors expect underpricing to earn initial return. Underpricing phenomena important researched because involve many factors. Aims of research determine effect of underwriter reputation, public accountant office reputation, size of company, financial leverage, last owner’s stock percentage and aims of using IPO’s fund to underpricing . Research in companies IPO at IDX period 2010-2014. Amount of sampel are 69 companies, used purposive sampling method. Data from prospectus and financial report.  Analysis technique used for research is multiple linear regression analysis. Based on research, found size of companies and financial leverage effect negative to underpricing, meanwhile the underwriter reputation, public accountant office reputation, last owner’s stock percentage and aims of using IPO’s fund to underpricing doesn’t effect to underpricing.
Keywords: underpricing, IPO, IDX